Pengawasan Hukum sebagai Benteng Pencegahan Pelanggaran Kampanye Pemilu - Latif, Asriadi; Dzulqarnain, Andi; Nur, Emil Fitra; Asriyadi, Asriyadi; Setawati, Elok; Karović, Sadmir (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This study discusses the role of legal supervision by the Election Supervisory Body (Bawaslu) in preventing election campaign violations, especially money politics practices, based on a normative analysis of Law Number 7 of 2017 concerning General Elections. Legal supervision has been proven to play an essential role in increasing the compliance of election participants and maintaining the integrity of the democratic process. However, the effectiveness of supervision still faces challenges in the form of limited resources, differences in legal interpretations, and low public awareness of the dangers of money politics. This study recommends strengthening institutional capacity, increasing synergy between institutions, and legal education for the public as strategic steps to create honest, fair, and trustworthy elections.